Determinants of User Trust in the National Electronic Payment System: An Empirical Study of the Edahabia System in Algeria - Boulenouar, Chahida (Journal of Excellence for Economics and Management Research, 2026)
This research quantifies the effect of technical reliability on Edahabia users’ trust, and then the effect of this trust on usage intention. A survey of 500 users in the Oran region, combined with transaction logs over 18 months, was analyzed using structural equation modeling. Technical reliability yields a standardized coefficient of 0.58 (p < 0.001) on trust; trust yields a coefficient of 0.68 (p < 0.001) on usage intention. Notable disparities appear according to residential area and socio-professional category. The results confirm that the system’s technical performance is the main determinant of user adoption